Relationship Between Oral Microorganisms and Dental Caries (Central Asian Journal of Medical Sciences, 2017)
Objectives: The purpose of this study was to investigate the relationship between the incidences of dental caries and the amount and motility of oral microorganisms in inter proximal dental plaque. Methods: Oral microorganism samples from 240 volunteers in six different age groups were classified according to morphology using phase contrast microscopy. We observed the amount and motility of the microorganisms and examined for relationships to the incidences of dental caries. Results: There was a statistically significant difference among the age groups (p < 0.05) in the motility of cocci and bacilli and in the amount of spirilla. The decayed tooth (DT), filled tooth (FT), and decayed, missing, filled tooth (DMFT) index for all age groups were calculated as 7.5 ± 4.5, 1.9 ± 3.0, and 14.8 ± 8.1. There was weak, positive relationship between the amount of cocci and bacilli and caries incidence, regardless of age (p < 0.01). Conclusion: Determining the amount and motility of oral microorganisms is an effective method of evaluating and controlling the status of oral health.